The role of nuclear factor kappa B signaling in the therapeutic effect of tadalafil against dexamethasone-induced gastric ulcer in rats - Elbadr, Mohamed; Sabra, Mahmoud; Ahmed, Doaa H.; Hassanein, Khaled; Saber, Ebtsam (Journal of Advanced Veterinary Research, 2024)
Gastric ulceration is a common gastrointestinal ailment with serious consequences that can lead to serious illness or even death. This study aimed to examine the efficacy of tadalafil (TAD) and dexlansoprazole (DLP) in treating stomach ulcers caused by dexamethasone (DEX) in male albino Wister rats. Thirty male albino Wister rats were divided into 5 groups (6 rats each): control group received normal saline, positive control group received DEX 5 mg/kg/day intraperitoneal (i.p.) for 7 days, the third group received DLP 30 mg/kg/day orally after DEX, the fourth group received TAD 5 mg/kg/day orally after DEX, and the fifth group received DLP and TAD orally after DEX. Persistence and prevention of ulcers, pepsin activity, mucin content, and histopathological changes were evaluated after each trial. Reduced glutathione (GSH), nitric oxide (NO), and malondialdehyde (MDA) levels were measured in gastric homogenates. Serum levels of prostaglandin E2 (PGE2), tumor necrosis factor-α (TNF-α), and interleukin-10 (IL-10) were also measured. Treatment with either TAD or DLP alone significantly reduced ulcer index (U.I.), pepsin activity, TNF-α, IL-10 and MDA with significant rise in mucin content, PGE2, NO, GSH, and improved the histological alteration compared to DEX group. When TAD and DLP were administered together, there was a more notable decrease in U.I., pepsin activity, gastric MDA, TNF-α, and IL-10 with concomitant more significant increase in mucin content, NO content, and PGE2 production compared to the TAD or DLP groups alone. Compared to each medicine alone, TAD and DLP together have promising therapeutic potential in preventing stomach ulcers caused by DEX.